Willingness Petani Menanam Bawang Putih: Bukti dari Kecamatan Sembalun, Nusa Tenggara Barat - Lalu Hendri Setiawan; Suprehatin; Marlina Ayuni Khosyati; Nurul Nazira; Siti Shara; Baiq Wardani Hidayati (Politeknik Negeri Lampung., 2022)
Farmer’s willingness to grow garlic, a high value horticulture crop, is one of the important factors to achive self-sufficiency. The purpose of this study is to analyze the willingness of farmers to grow garlic and its determinant factors using theory of planned behavior (TPB) approach. This study used a primary data from a survey of 157 garlic farmers in Sembalun subdistrict as one of the center of garlic production in Indonesia. Data were analysed using scoring and Structural Equation Modeling-Partial Least Square (SEM-PLS). The result showed that willingness of Sembalun farmers to grow garlic is at a moderate level. The result also showed that attitude, subjective norms, and behavioral control of Sembalun farmers have a positif and significant effect on their willingness to grow garlic. This study recommends that increasing the willingness of farmers can be achieved by formulating a strategy using both internal and external factors in the micro, meso and macro levels.